FUNGSI MANAJERIAL KEPALA MADRASAH DALAM MENCIPTAKAN MADRASAH EFEKTIF DI MTS DI MTS AL MUHAJIRIN PEMATANG PASIR LAMPUNG SELATAN - Dwi Efendi (UNISAN JURNAL, 2022)
: The purpose of this study was to describe and analyze the managerial head of Madrasah regarding planning, organizing, directing and controlling so as to create an effective Madrasah. This research uses descriptive qualitative method. The data sources of this research are the head of Madrasah (as key informant), deputy head of Madrasah, teachers, parents (school committee) and administration (as informant). Data collection techniques through observation, interviews, and documentation. Analysis of research data was carried out through the following steps: (1) collecting data, (2) reducing data, (3) presenting data, and (4) drawing conclusions. The results of the research are: 1) the managerial ability of the Madrasah principal in planning to create an effective Madrasah in accordance with the criteria of an effective Madrasah, the managerial ability of the Madrasah principal in organizing an effective Madrasah according to procedures, 2) The madrasah principal’s managerial ability in guiding to create an effective Madrasah has also been going well., Managerial ability Control or supervision carried out by the head of Madrasah in creating effective Madrasahs by monitoring and evaluating. From the overall managerial head of Madrasah, it can be stated that the Madrasah principal of MTs Al Muhajirin Lampung Selatan has been able to create an effective Madrasah because it has implemented effective Madrasah indicators that refer to Madrasah inputs, processes, outputs and outcomes.